Increased nerve density adversely affects outcome in colorectal cancer and denervation suppresses tumor growth - Hao Wang; Ruixue Huo; Kexin He; Weihan Li; Yuan Gao; Wei He; Minhao Yu; Shu-Heng Jiang; Junli Xue (Journal of Translational Medicine)
Abstract Background The colon and rectum are highly innervated, with neural components within the tumor microenvironment playing a significant role in colorectal cancer (CRC) progression. While perineural invasion (PNI) is associated with poor prognosis in CRC, the impact of nerve density and diameter on tumor behavior remains unclear. This study aims to evaluate the prognostic value of nerve characteristics in CRC and to verify the impact of nerves on tumor growth. Methods Tissue samples from 129 CRC patients were stained with immunofluorescent markers NF-L and S100B to detect nerves. Nerve diameter and density were measured and normalized. Kaplan-Meier survival analysis and Cox regression models were used to identify prognostic factors. Prognostic models were established using receiver operating characteristic (ROC) curve analysis to assess the predictive value of neural factors. A murine chemical denervation model was employed to disrupt sympathetic nerves using 6-hydroxydopamine, inhibit muscarinic receptor 3 with darifenacin, and ablate sensory neurons with capsaicin. Results The total nerve density was 0.72 ± 0.59/mm², with intratumoral (0.42 ± 0.40/mm²) being significantly lower than extratumoral regions (1.00 ± 0.75/mm²). The average nerve diameter was 28.14 ± 6.04 μm, with no significant difference between intratumoral (28.2 ± 7.65 μm) and extratumoral regions (27.86 ± 6.72 μm). PNI was observed in 65 patients (50.4%). PNI and high normalized nerve density (NND) were associated with shorter overall survival and disease-free survival in CRC patients, with PNI identified as an independent prognostic factor. Patients with PNI exhibit higher NND. Incorporating PNI and NND into ROC curve analysis improved the sensitivity and specificity of survival predictions. In the murine model, chemical denervation of sympathetic, parasympathetic, and sensory nerves significantly reduced rectal tumor volume. Conclusions PNI and NND are critical factors influencing CRC patient survival and enhance the accuracy of survival prediction models. Moreover, chemical denervation effectively inhibits rectal tumor growth in vivo, highlighting the potential of neural targeting as a therapeutic strategy in CRC.